Expression pattern of miR-451 and its target MIF (macrophage migration inhibitory factor) in colorectal cancer. Issue 4 (9th September 2016) - Mamoori, Afraa; Gopalan, Vinod; Lu, Cu-Tai; Chua, Terence C; Morris, David L; Smith, Robert Anthony; Lam, Alfred K-Y
Abstract : Aims: To investigate the expression pattern of microRNA-451 (miR-451) in patients with colorectal carcinoma and correlate with the expression of its target gene MIF ( macrophage migration inhibitory factor ). Methods: Matched cancer and non-cancer fresh frozen tissues were prospectively collected from 70 patients (35 men and 35 women) who underwent resection of colorectal adenocarcinoma. These tissues collected were extracted for miR and complementary DNA conversion. Then, miR-451 expressions in these tissues were measured by quantitative real-time PCR. The expression was correlated with clinical and pathological parameters of these patients. In addition, paraffin blocks of 10 colorectal carcinomas with lowest expression of miR-451 were used for the study of MIF protein expression by immunohistochemistry. Results: miR-451 was downregulated in majority of the colorectal cancer tissues when compared with their matched normal tissues (84.3%, n=59/70). Downregulation of miR-451 correlates significantly with presence of coexisting adenoma (91.4%, p=0.025). In addition, persistence of cancer or cancer recurrence after surgery showed significant correlation with downregulation of miR-451 (80% vs 0%; p=0.028). There is no significant correlation between miR-451 expression and age, gender of the patients as well as size, grades, pathological stages, presence of lymphovascular permeation, perineural invasion and microsatellite instability status of the colorectal carcinoma (p>0.05). Majority of the cases (80%) with low expression of miR-451 showed high levels of MIF protein expression confirming the inverse relationship between miR-451 and MIF expressions. Conclusions: The results showed that miR-451 could play a role in development and progression of colorectal cancer and likely by targeting MIF .